2023
DOI: 10.5902/1980509848302
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da madeira e do carvão vegetal de quatro clones de <i>Eucalyptus</i> com idades entre 108 e 120 meses

Abstract: Cenários de instabilidade econômica e redução do consumo de carvão vegetal, como as ocorridas em 2009 e 2016, afetam a produção deste insumo, resultando na manutenção das florestas de eucalipto e aumento da idade de corte. O objetivo deste trabalho foi avaliar a qualidade da madeira de quatro clones de Eucalyptus (clones 1, 2, 3 e 4) com idades entre 108 e 120 meses e do carvão vegetal produzido em forno retangular. Para caracterização da madeira, foram avaliadas a relação cerne/alburno, densidade básica, mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The highest residual mass values above 450°C were observed for E. urophylla 2 and E. cloeziana clones. Therefore, such clones have the necessary structure to withstand mass loss in industrial carbonization processes, whose fi nal temperatures reported in the literature are between 350°C and 400°C (Donato et al, 2020;Figueiró et al, 2019;Ramos et al, 2023), providing higher charcoal yields. However, the residual mass observed for the wood of the other clones was greater than that found for the wood of the clones evaluated in the literature (Pereira et al, 2013b;Santos et al, 2012) whose charcoal produced had a satisfactory gravimetric yield.…”
Section: Thermal Properties Of Woodmentioning
confidence: 99%
“…The highest residual mass values above 450°C were observed for E. urophylla 2 and E. cloeziana clones. Therefore, such clones have the necessary structure to withstand mass loss in industrial carbonization processes, whose fi nal temperatures reported in the literature are between 350°C and 400°C (Donato et al, 2020;Figueiró et al, 2019;Ramos et al, 2023), providing higher charcoal yields. However, the residual mass observed for the wood of the other clones was greater than that found for the wood of the clones evaluated in the literature (Pereira et al, 2013b;Santos et al, 2012) whose charcoal produced had a satisfactory gravimetric yield.…”
Section: Thermal Properties Of Woodmentioning
confidence: 99%